Hematological Abnormalities in Neonates Diagnosed with Neonatal Sepsis (Medical Forum Monthly, 2026)
Objective: To determine the mean value of hematological parameters including red blood cell distribution width, platelet distribution width, mean platelet volume, white blood cell count, red blood cell count and platelet count in neonates diagnosed with neonatal sepsis.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Pediatric Medicine, Sahiwal Teaching Hospital, Sahiwal from 1st February 2025 to 31st July 2025.Methods: In this study 70 neonates were enrolled. Blood samples were taken in a 3cc disposable syringe and sent to the laboratory for assessment of hematological parametersResults: The mean age was 11.6±7.4 days, and 39 (55.7%) neonates were males. Early-onset sepsis was present in 42 (60%) cases. Raised red cell distribution width was observed in 46 (65.7%) neonates, abnormal white blood cell count in 38 (54.3%), raised platelet distribution width in 39 (55.7%), raised mean platelet volume in 34 (48.6%), and thrombocytopenia in 29 (41.4%). Late-onset sepsis was associated with significantly higher red cell distribution width, platelet distribution width, and mean platelet volume and a significantly lower platelet count.Conclusion: Hematological abnormalities were frequent among neonates with sepsis. Red cell and platelet indices may provide useful supportive information, particularly in neonates with late-onset sepsis and low birth weight.